Eosinophilic Myocarditis With Hypersegmented Granulocytes and Neutrophilia Without Eosinophilia: A Case Mimicking Neutrophilic Myocarditis. (October 2018) - Hashimoto, Hirotsugu; Hashikata, Takehiro; Shindo, Akito; Horiuchi, Hajime
We report a case of a 78-year-old woman with neutrophilia without eosinophilia who was pathologically diagnosed with eosinophilic myocarditis by myocardial biopsy. The biopsy specimen showed infiltrating granulocytes with hypersegmentation, mimicking neutrophils; however, they were confirmed to be eosinophils by Giemsa staining.